Proceedings of the 14th ACM Multimedia Systems Conference 2023
DOI: 10.1145/3587819.3592559
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual annotation of local distortions in videos: tools and datasets

Abstract: To assess the quality of multimedia content, create datasets, and train objective quality metrics, one needs to collect subjective opinions from annotators. Different subjective methodologies exist, from direct rating with single or double stimuli to indirect rating with pairwise comparisons. Triplet and quadruplet-based comparisons are a type of indirect rating. From these comparisons and preferences on stimuli, we can place the assessed stimuli on a perceptual scale (e.g., from low to high quality). Maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In [6,[8][9][10], the authors suggested examining the MOS discriminability evolution with increasing numbers of assessors to show how well a subjective methodology can recover accurate MOS scores and compare subjective methodologies efficiency [33]. A two-sample Wilcoxon test is applied to all the possible pairs of MOS in a dataset to test the proportion of significantly different ones.…”
Section: Discriminability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In [6,[8][9][10], the authors suggested examining the MOS discriminability evolution with increasing numbers of assessors to show how well a subjective methodology can recover accurate MOS scores and compare subjective methodologies efficiency [33]. A two-sample Wilcoxon test is applied to all the possible pairs of MOS in a dataset to test the proportion of significantly different ones.…”
Section: Discriminability Analysismentioning
confidence: 99%
“…Based on these data, we will demonstrate how rendering setup and subjective test methodologies affect the quality of subjective data in terms of discriminability [6,[8][9][10][11]. This is an important aspect of codec development and standardization activities, as system performances must be evaluated and compared.…”
Section: Introductionmentioning
confidence: 99%